Student Loans Financing in Tanzania:: Who Benefits and How - Dachi, Hillary A. (International Journal of African Higher Education, 2021)
This study examined the mechanisms employed to finance student loans in Tanzania and who benefits and how. The findings show that student loans are financed by the public exchequer. The number of students from high-income families accessing these loans is disproportionate to their representation in Higher Education Institutions, while the share for middle and low-income students reflects their representation. There is also an imbalance between male and female beneficiaries across programmes, notably in the Science, Technology, Engineering, and Math (STEM) disciplines. It is concluded that such disparities are the result of the fact that the student loan scheme seeks to satisfy a number of government policy objectives in relation to higher education beyond access and equity, and that means testing is not rigorously conducted. Key words: Higher Education, higher education policy, financing higher education, higher education student loans, public subsidisation of higher education